Estrategias didácticas interculturales y su influencia en el aprendizaje de vocabulario en los idiomas “Kichwa-Inglés” en los estudiantes del CECIBEB “Países Andinos” - Achic Margaritax, Asadobay Pagalo (2021)
ABSTRACT The research “INTERCULTURAL DIDACTIC STRATEGIES AND THEIR INFLUENCE ON THE LEARNING OF VOCABULARY IN "KICHWA-ENGLISH" LANGUAGES AT CECIBEB “PAÍSES ANDINOS”, students, has the objective of proposing didactic strategies in the initial learning of the basic vocabulary in Kichwa and English languages in order to improve the lexicon of both languages and the development of language skills. The research was structured and focused on foundations: scientific, philosophical, epistemological, pedagogical, legal, psychological and theoretical. The theoretical framework is structured with topics and subtopics related to the independent variable that are intercultural didactic strategies that consists of methods, techniques and activities proposed for teaching; and the dependent variable with the development of the vocabulary of the Kichwa and English languages, which consists of a basic lexicon such as: imperatives, greetings, numbers, family, food, clothing, times, animals, among other topics. The methodology was based on a mixed approach. The technique used for the first variable was the interview with questions directed at key informants and for the second variable it was the survey with the knowledge tests instrument with closed questions. A defined population of 40 students from CECIBEB “Países Andinos”, there was no sample due the reduced number of students. Within the presentation and discussion of the results, the data obtained through the evaluation of knowledge regarding the mastery of vocabulary in the Kichwa-English languages in the students were processed to be tabulated and organized in tables and statistical graphs with their respective percentages. In addition, the systematization and analysis of the interviews of key informants in which the pedagogical and didactic needs that teachers have for teaching the lexicon were collected. As a result, mention is made of the need to implement didactic strategies for teaching and learning of Kichwa-English vocabulary from an integrated perspective that is the pedagogical proposal of the MOSEIB (Model of the Intercultural Bilingual Education System), jurisdiction to which the educational center in which the research was carried out. In this way, by integrating the learning of the two languages, it is intended to strengthen interculturality inside and outside the classroom. On the one hand, strengthening the mother tongue as the language of the Kichwa nationality; on the other hand, motivating the learning of a foreign language as a second language and intercultural relations. For this reason, a guide for students and a didactic orientation guide for teachers were developed, which were validated by experts on the subject. Keywords: Strategies, vocabulary, bilingual, interculturality. Reviewed by; Inca Jhon English Teacher: